2011
DOI: 10.1094/phyto-04-11-0100
|View full text |Cite
|
Sign up to set email alerts
|

Comments Regarding the Binary Power Law for Heterogeneity of Disease Incidence

Abstract: The binary power law (BPL) has been successfully used to characterize heterogeneity (overdispersion or small-scale aggregation) of disease incidence for many plant pathosystems. With the BPL, the log of the observed variance is a linear function of the log of the theoretical variance for a binomial distribution over the range of incidence values, and the estimated scale (?) and slope (b) parameters provide information on the characteristics of aggregation. When b = 1, the interpretation is that the degree of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Given that the BPL provides a good description of the heterogeneity of numerous empirical and theoretical data sets across spatiotemporal scales [as recently reviewed in Turechek et al . (), and previously in Madden & Hughes () and Madden et al . ()], two questions naturally arise: (i) what is the extent of the conditions under which the simple BPL relationship, or somewhat more complex ABPL, holds?…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…Given that the BPL provides a good description of the heterogeneity of numerous empirical and theoretical data sets across spatiotemporal scales [as recently reviewed in Turechek et al . (), and previously in Madden & Hughes () and Madden et al . ()], two questions naturally arise: (i) what is the extent of the conditions under which the simple BPL relationship, or somewhat more complex ABPL, holds?…”
Section: Introductionsupporting
confidence: 66%
“…Given the generality of the BPL results across many plant diseases, several mechanisms based on environmental, biological, physical and demographic stochasticity are likely to be responsible for the BPL (Turechek et al ., ). Stochastic simulations based on a spatially explicit model of plant diseases have shown that the BPL (Eqn , with b > 1) arises naturally over a wide range of epidemiological conditions (Xu & Ridout, , ).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations